Participatory Approaches - Guijt, Irene (UNICEF, 2014)
This guide, written by Irene Guijt for UNICEF, looks at the use of par ticipatory approaches in impact evaluation. Using participatory approa ches means involving stakeholders, particularly those affected by inte rvention, in the evaluation process. This includes involvement in the design, data collection, analysis, reporting, and management of the st udy. Excerpt "By asking the question, ‘Who should be involved, why and how?’ for each step of an impact evaluation, an appropriate and conte xt-specific participatory approach can be developed. Managers of UNICE F evaluations must recognize that being clear about the purpose of par ticipatory approaches in an impact evaluation is an essential first st ep towards managing expectations and guiding implementation. Is the pu rpose to ensure that the voices of those whose lives should have been improved by the programme or policy are central to the findings? Is it to ensure a relevant evaluation focus? Is it to hear people’s own ver sions of change rather than obtain an external evaluator’s set of indi cators? Is it to build ownership of the UNICEF programme? These, and o ther considerations, would lead to different forms of participation by different combinations of stakeholders in the impact evaluation."